(Once Again) On the Concept of Security and the Sketch of the Modified Securitization Theory - Petrović, Dejan (Sociološki pregled, 2025)
The main subject of consideration is the concept of security. However, the conceptual analysis is carried out in a specific way, namely through the presentation of a rough outline of the popular theory’s modification. Security is viewed as a value whose existence is linked to the preservation of the established value system of a given society, which is used as a basis for further reflection on the nature of the relationship between security and ideology. The standpoint that security, as a value, can be easily integrated into existing ideological systems allows it to be the subject of Althusser’s ideological state apparatuses. By using the theories of the state and ideology of the French philosopher, this paper aims to overcome the main shortcomings of the theory of securitization, namely the weak visibility of structural factors that enable the realization of the mentioned process.